The psychological impact of COVID-19 lockdown on medical student’s education - Siddiqui, Subata; Siddiqui, Atif Hafeez; Jafri, Sumaiya; Siraj Memon, Amjad (International Journal of Endorsing Health Science Research, 2021)
Background: The COVID-19 lockdown has severely affected all aspects of life, including medical students. The present study was designed to gain perspective on how the COVID-19 lockdown has affected Karachi's medical student's study patterns and mental health. Methodology: Undergraduate students from twelve medical colleges participated in this cross-sectional survey. A self-administered online survey form was sent to 1000 medical students via WhatsApp and other social media platforms. A total of 670 responses were received. Questions regarding the psychological impact of lockdown and wellbeing concerns about the future during lockdown were part of this survey. The Hamilton Anxiety Rating Scale was used to determine the level of anxiety in students. Results: According to our survey, 270 (40.8%) medical students who participated in the survey have been severely affected, where 392 students (60.1%) either did not study daily or spent less than 2 hours studying on average. This situation has also taken a severe toll on their mental health as 314 (47.4%) students proved to have anxiety, a feeling of irritation and uneasiness most of the time during the day. Many students, 439 (66.3%), also faced difficulty concentrating while doing menial tasks or studying. Conclusion: Most students faced a severe loss of study and showed anxiety and depression symptoms during the lockdown period.